Toward a knowledge model focusing on microservices and cloud computing. (18th June 2019) - Apel, Sebastian; Hertrampf, Florian; Späthe, Steffen
Summary: Microservices tend to use a variety of tools to create a well‐defined process of building, packing, backing, and publishing. These tools are usually configured independently by their descriptors. Interrelations between the different tools arise implicitly, but the overall structure only works if the different configurations are correctly coordinated along each other. This paper motivates the development of a knowledge model via a microservice measurement infrastructure within the research project WINNER, which explicitly shapes these interrelationships. For the development of our infrastructure‐related work, experience and requirements of currently common tools are used as a basis. The model contains essential structures for the description of configurations and endpoints, artefacts, and connections for the creation as well as publication process of services result. Our results are applied and discussed in an example.